2023
DOI: 10.3390/ma16083097
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in Plants: Uptake, Transport and Physiological Activity in Leaf and Root

Abstract: Due to their unique characteristics, nanoparticles are increasingly used in agricultural production through foliage spraying and soil application. The use of nanoparticles can improve the efficiency of agricultural chemicals and reduce the pollution caused by the use of agricultural chemicals. However, introducing nanoparticles into agricultural production may pose risks to the environment, food and even human health. Therefore, it is crucial to pay attention to the absorption migration, and transformation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(40 citation statements)
references
References 146 publications
2
38
0
Order By: Relevance
“…A potential path for root entry could be parent root wound generated from root hair fall followed by lateral root emergence . However, other routes such as semipermeable epidermis can also play an active role in MSN uptake . Further studies are needed to explore how the MSNs stick to the root surface and/or root wounds, enabling their cellular entry.…”
Section: Uptake and Translocation Of Pesticide-loaded Psnsmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential path for root entry could be parent root wound generated from root hair fall followed by lateral root emergence . However, other routes such as semipermeable epidermis can also play an active role in MSN uptake . Further studies are needed to explore how the MSNs stick to the root surface and/or root wounds, enabling their cellular entry.…”
Section: Uptake and Translocation Of Pesticide-loaded Psnsmentioning
confidence: 99%
“…185 However, other routes such as semipermeable epidermis can also play an active role in MSN uptake. 186 Further studies are needed to explore how the MSNs stick to the root surface and/or root wounds, enabling their cellular entry.…”
Section: Uptake and Translocation Of Pesticide-loaded Psnsmentioning
confidence: 99%
“…Inorganic NDVs in a similar size range have been shown to be internalized by plant cells as well. Following administration to whole plants, inorganic zinc oxide nanoparticles up to 40 nm were imaged at the cell wall of rice plants , and ∼200 nm silica oxide nanoparticles encapsulating pesticides have been shown to increase the elasticity and expand cell wall pores in cucumber plants. , …”
Section: Cellular Internalization and Transport Mechanismsmentioning
confidence: 99%
“…Previous reviews on inorganic NDVs have identified size, surface charge, surface chemistry, and plant species as major factors governing foliar uptake and translocation. 95,24,14 In the sections that follow, trends for organic NDVs are presented and then compared with trends reported for inorganic NDVs. 4.1.…”
Section: Foliar Application Of Organic Ndvsmentioning
confidence: 99%
See 1 more Smart Citation